Aksiologi: Antara Etika, Moral, dan Estetika - Totok Wahyu Abadi (Universitas Muhammadiyah Sidoarjo, 2016)
Science is essentially neutral. The neutrality of science depends on man. Ontologically and axiologically, it is man who determines and gives judgments about good and bad. Einstein says that science without religion is blind, and religion without knowledge is paralyzed. For that, in the axiological side, science must make a more useful contribution to human life. This paper explain how axiology as one of the main pillars of philosophy reveals issues of value, ethics, morals, and aesthetics.